Tumor Budding, uPA, and PAI-1 in Colorectal Cancer: Update of a Prospective Study. (12th February 2017) - Märkl, Bruno; Hardt, Jochen; Franz, Simon; Schaller, Tina; Schenkirsch, Gerhard; Kriening, Bernadette; Hoffmann, Reinhard; Rüth, Stefan
Abstract : Aims . The prognostic role of the proteases uPA and PAI-1, as well as tumor budding, in colon cancer, has been investigated previously. Methods . We provide 6-year follow-up data and results of the validation set. The initial test set and validation set consisted of 55 colon cancers and 68 colorectal cancers, respectively. Tissue samples were analyzed for uPA and PAI-1 using a commercially available Enzyme-Linked Immunosorbent Assay (ELISA). Tumor budding was analyzed on cytokeratin-stained slides. Survival analyses were performed using cut-offs that were determined previously. Results . uPA was not prognostic for outcome. PAI-1 showed a trend towards reduced cancer specific survival in PAI-1 high-grade cases (68 versus 83 months; P = 0.091 ). The combination of high-grade PAI-1 and tumor budding was associated with significantly reduced cancer specific survival (60 versus 83 months; P = 0.021 ). After pooling the data from both sets, multivariate analyses revealed that the factors pN-stage, V-stage, and a combination of tumor budding and PAI-1 were independently prognostic for the association with distant metastases. Conclusions . A synergistic adverse effect of PAI-1 and tumor budding in uni- and multivariable analyses was found. PAI-1 could serve as a target for anticancer therapy.